Moisture content evaluation of biomass using CFD approach (Scientia Agricola, 2012)
In grass conservation systems, drying in the field is an essential process upon which the quality and quantity of the material to be conserved is dependent on. In this study a Computational Fluid Dynamics (CFD) model, previously validated, was used to assess qualitatively and quantitatively the field drying process of cut grass under different weather conditions and structural specifications of the grass. The use of the CFD model depicts the climate heterogeneity in the grass area with a special focus on moisture distribution, influence of the weather conditions, in order to create the possibility of applying the model as a decision support tool for an enhanced treatment of the grass after cutting.